Current Aspects of Antiepileptic Therapy in Pregnant Women - S. R. Zoirov; M. A. Artykova (Universitas Muhammadiyah Sidoarjo, 2022)
Achieving a high quality of life in patients with epilepsy is of paramount importance not only for neurologists, but also for allied professionals who guide patients through the subsequent stages of treatment after diagnosis. This is of particular relevance to patients in the gestational period. Literature suggests that 13% of women experience an exacerbation of epilepsy during pregnancy, which is due to a reduction in plasma levels of antiepileptic drugs (PEPs) due to increased metabolism. However, 14% of women have seizures exclusively during pregnancy.